Pendidikan Politik Bagi Pemilih Menjelang Pemilu Serentak 2019 - Anang Dony Irawan (Fakultas Ilmu Sosial dan Hukum, Universitas Negeri Surabaya, 2019)
The existence of the Constitutional Court Decision Number 14 / PUU-XI / 2013 in the trial case of Law Number 42 Year 2008 concerning General Elections of the President and Vice President whose decisions are final states that the holding of the 2019 General Elections and the subsequent General Elections shall be held simultaneously. The idea of holding a simultaneous General Election in 2019 certainly had a political impact, both nationally and regionally. The ruling of the Constitutional Court gave birth to Law Number 7 of 2017 concerning General Elections. This has had a huge impact and challenge for the Indonesian people in improving the electoral system and implementing a better democracy. The purpose of this study is to find out how to realize political education for voters ahead of the 2019 simultaneous elections. This study is a juridical normative approach to legislation. From the results of the study there is a legal vacuum that requires the General Election Commission to conduct Socialization, Voter Education, and Community Participation in the 2019 Election. In the Regional Head Election process there are technical rules governing the Socialization, Voter Education, and Community Participation, but do not include the threat of sanctions if it does not carry out the said activity. The resulting conclusion is that political education for voters ahead of the 2019 concurrent elections is very important to carry out, as an effort to realize the Sovereignty of a Strong State. The resulting recommendation is to make a legal rule regarding the obligation to carry out political education for voters ahead of the 2019 simultaneous elections as an effort to realize the Strong Sovereign State Voters in the 2019 Election along with the threat of sanctions for election administrators in an Act.Keywords: 2019 Election, Voter Education, Strong Sovereign State Voters.